Foreword - Zakharova, Anna V.; Mal’tseva, Svetlana V.; Staniukovich-Denisova, Ekaterina Yu. (Actual Problems of Theory and History of Art, 2016)
The article is an introduction of collection of articles publishing the materials of the 6th International Conference “Actual Problems of Theory and History of Art” held in Moscow on October 27-31, 2015. The articles in Russian and in English present the results of research in the art of the Ancient World, Byzantium, Western Europe and Russia from the Middle Ages to the 21st c. and theory of art. The edition is addressed to art historians, historians, art students and art lovers.